2013
DOI: 10.1016/j.ibiod.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Multiple degradation pathways of phenanthrene by Stenotrophomonas maltophilia C6

Abstract: Stenotrophomonas maltophilia strain C6, capable of utilizing phenanthrene as a sole source of carbon and energy, was isolated from creosote-contaminated sites at Hilo, Hawaii. Twenty-two metabolites of phenanthrene, covering from dihydrodiol to protocatechuic acid, were isolated and characterized. Phenanthrene was degraded via an initial dioxygenation on 1,2-, 3,4-, and 9,10-C, where the 3,4-dioxygenation and subsequent metabolisms were most dominant. The metabolic pathways were further branched by ortho- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 39 publications
2
41
1
1
Order By: Relevance
“…In this experiment, a range of 45-110 lg mL -1 of cell pellet protein concentration was recorded within 10-20 days of incubation. S. maltophilia strain C6 also reported for utilization of Phenanthrene as a sole carbon and energy source [9]. In case of S. maltophilia BR-12, maximum amount of cell pellet and soluble protein (50 lg mL -1 ) was recorded between 15 and 20 days of growth.…”
Section: Evaluation Of Biosurfactant Production and Pyrene Degradationmentioning
confidence: 92%
See 1 more Smart Citation
“…In this experiment, a range of 45-110 lg mL -1 of cell pellet protein concentration was recorded within 10-20 days of incubation. S. maltophilia strain C6 also reported for utilization of Phenanthrene as a sole carbon and energy source [9]. In case of S. maltophilia BR-12, maximum amount of cell pellet and soluble protein (50 lg mL -1 ) was recorded between 15 and 20 days of growth.…”
Section: Evaluation Of Biosurfactant Production and Pyrene Degradationmentioning
confidence: 92%
“…Among various biosurfactant producing microorganisms S. maltophilia is known to degrade number of PAHs including Phenenthrene, Benzopyrene, Benzophenanthrene, and Anthracene etc. [9,13]. In this study, a bacterial isolate BR-12 isolated from Vadodra oil refinery soil with biosurfactant production capability was evaluated for biodegradation of Pyrene with an aim to produce an effective bioremediation strategy for such contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…USTB-RU degrading PHE via protocatechuate pathway. PHE degradation by the strain Stenotrophomonas maltophilia C6 has been proposed as protocatechuate and salicylate pathway (Gao et al, 2013). Seo et al (2012) reported a highly branched metabolic pathways of PHE biodegradation, including dioxygenation on C-1, 2 and C-3,4 and C-9,10 positions and ring opening by both ortho-and meta-cleavage by Mycobacterium aromativorans strain JS19b1…”
Section: Degradation Of Phenanthrenementioning
confidence: 99%
“…Due to their adaptability, rapid population growth and highly efficient metabolism, microorganisms are accepted as a significant role in treating those PAHs contaminated sites (Roy et al, 2012). Phenanthrene (PHE), a tricyclic aromatic hydrocarbon with three-fused rings in an angular fashion, is commonly used as a model compound for PAH biodegradation studies (Roy et al, 2012;Gao et al, 2013). Halophilic or halotolerant PHE-degrading bacteria have the capability of using PHE as a source of carbon and energy (Bogan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Chitinophagaceae was dominant with 40.9% for pyrene. Moreover, several authors [36,51,52] have conducted research presenting Stenotrophomonas as excellent candidates for PAH removal, particularly phenanthrene. Table 4 shows Stenotrophomonas as the dominant group in the phenanthrene sample with a 23% presence.…”
Section: Resultsmentioning
confidence: 99%